Variability in the distance from the end of the gray matter to the end of the conus medullaris: a case-triggered histological investigation. - Scheer, Maximilian; Griesler, Bruno; Ottlik, Elisabeth; Strauss, Christian; Mawrin, Christian; Kunze, Christian; Prell, Julian; Rampp, Stefan; Simmermacher, Sebastian; Illert, Joerg; Kielstein, Heike; Scheller, Christian (Journal of Neurosurgery-Spine, 2021)
OBJECTIVE: The background for this investigation was the dramatic course of a 14-year-old girl with a spontaneous hemorrhage in the area of the conus medullaris resulting in a complete cross-sectional syndrome with bladder and bowel dysfunction. Despite immediate surgical treatment, the patient showed close to no postoperative improvement. Subsequent histopathological examination of the removed masses revealed a cavernoma. To better understand the link between the site and symptoms of conus medullaris lesions, the authors performed a literature search and then histological examination of the conus medullaris of 18 cadaveric specimens from body donors. METHODS: After a literature search regarding the histological features of the structure of the conus medullaris did not lead to satisfying results, the authors performed histological examination of the conus medullaris in 18 cadaveric specimens from body donors. The largest (a) and smallest (b) diameters of the conus medullaris were measured, noting individual variations in the distance from the caudal ending of the gray matter to the macroscopically visible end of the conus medullaris. Correlations of these differences with sex, body height, gray matter transverse diameter, and cross-sectional area at the end of the gray matter were analyzed. RESULTS: Gray matter displayed in the form of a butterfly figure was found along almost the entire length of the conus medullaris. The specific slide containing the end of the gray matter was noted. The distance between the caudal ending of the gray matter in the conus and the macroscopical end of the conus medullaris was defined as the gray matter to cone termination (GMCT) distance. There were great individual variations in the distance from the caudal ending of the gray matter to the macroscopically visible end of the conus medullaris. Analysis of the correlations of these differences with sex, body height, gray matter transverse diameter, and cross-sectional area at the end of the gray matter showed no significant sex-specific differences in the GMCT distance. Patient body height and transverse diameter at the end of the gray matter were found to be correlated positively with the GMCT distance. Moreover, greater height also correlated positively with the cross-sectional area at the end of the gray matter. CONCLUSIONS: This report is, to the authors' knowledge, the first published description of the histological structure of the conus medullaris and can serve as the basis for a better understanding of neurological deficits in patients with a conus medullaris syndrome. Findings that gray matter can be detected far into the conus medullaris, with large individual differences in the endpoint of the gray matter, are important for operative care of intramedullary masses and vascular malformations in this area. It is therefore important to use electrophysiological monitoring during these operations.
EVALuna2:500102